O futebol além das quatro linhas: mercadorização - sociabilidades e o ciclo de reconversão precoce - Trizoto, Henrique Antônio (2018)
Soccer has become a rich field of research, which has surpassed the idea of a physical culture, encompassing historical, geographic, economic, sociological, identity and anthropological elements, enabling us to work as an object of academic research with endless nuances. The present research brings to the scene a theme little studied and debated where we try to explain some of the transformations that the soccer has passed in the last years. From a bibliographical review, and the completion of four interviews with former professional athletes who, even at age compatible with high-level practice of sport are working in other sectors of the economy for survival purposes, which maintains the "form" and the dream live on weekends, participating in the Municipal Field Soccer Championship 1st Division of Erechim in 2016. Interviews that help in understanding how the formation of the sociability of these players was influenced by these transformations, and in what way permeated these constructions, mainly with regard to this professionalization / failure / reinsertion in the labor market, from a few key questions: How was the formation of players' sociability influenced by the process of commodification that occurred from the 1980s? What elements permeated this process? In what way was the dream of professionalization influenced by the scenario of the period? With the tabulation of the data, it is noticeable, that football is still part of his imagination, as well as helped in the construction of his personalities.